The Concept of Communication in Linguistics And Its Types - F.T.Temirova (Euro Asian Journal Publishing, 2023)
Communication, as a socio-psychological phenomenon, takes part in all spheres of social life and arises as a need for material, spiritual, cultural, emotional, motivational aspects of cooperation. Satisfying the various needs that arise in a person depends on the ritual of communication, and interpersonal relations serve to establish the ideals of a perfect generation and a perfect person. The basis of the success of communication is the manifestation and development of qualities, qualities such as a person's spiritual world, needs, motivation, character traits, individual-typological characteristics, abilities, beliefs. Communication prepares a thorough ground for self-correction, reeducation, realization of personal potential on the basis of external positive influences and examples.
Keywords: communication; kinetics; paralinguistics; proxemics